Light-driven friction reversible transformation film and preparation method thereof

Through the photoisomerization characteristics of the silane single-layer fiber membrane functionalized by azobenzene, a method of precisely controlling friction force on the nanoscale is realized, solving the problem of difficulty in controlling the friction force of nanomaterials in the prior art, and achieving the reversible friction transformation effect of light-driven.

CN119567650AActive Publication Date: 2025-03-07QILU UNIVERSITY OF TECHNOLOGY (SHANDONG ACADEMY OF SCIENCES)
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
CN202411730762.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-03-07
Estimated Expiration
2044-11-29

Smart Images

  • Figure CN119567650A_ABST
    Figure CN119567650A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of nano materials, and discloses a light-driven friction reversible transformation membrane and a preparation method thereof.The friction reversible transformation membrane comprises an azobenzene functionalized silane single-layer fiber membrane, and the azobenzene functionalized silane single-layer fiber membrane comprises an azobenzene sulfonyl chloride compound and a substrate; the azobenzene sulfonyl chloride compound comprises an azobenzene group and a sulfonyl chloride group which are connected with each other. The conformation of the azobenzene functionalized silane single-layer fiber membrane is changed by irradiating different light and applying mechanical force, and the friction property of the membrane is also changed after isomerization, so that light-driven friction reversible transformation is realized, and the azobenzene functionalized silane single-layer fiber membrane can be widely applied to nanoscale electromechanical and photoelectric devices needing friction regulation and control and has a good application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of nanomaterials and relates to a light-driven friction reversible conversion film and a preparation method thereof. Background Art

[0002] With the rapid development of nanotechnology and optical technology, nano-scale electromechanical and optoelectronic devices emerge in an endless stream. Friction phenomena have a crucial impact on the performance, life and reliability of devices. The existence of friction can provide the necessary stability and control force under certain circumstances, but may also lead to energy loss, wear and functional failure in some cases. Therefore, reasonable control of the magnitude of friction is one of the key technologies for optimizing high-performance nano-scale electromechanical and optoelectronic devices. The existing technology mostly uses the use of lubricants, surface texturing, replacement of materials with different friction coefficients, etc., but there are still difficulties in accurately controlling the friction of materials at the nanoscale, and it is difficult to achieve simple and rapid regulation of the friction of materials in complex environments. Summary of the invention

[0003] In view of the above-mentioned deficiencies in the prior art, an object of the present invention is to provide a light-driven friction reversible conversion film and a method for preparing the same.

[0004] In order to solve the above technical problems, the present invention provides the following technical solutions:

[0005] A light-driven friction reversible conversion film, the film comprising an azobenzene-functionalized silane monolayer fiber film, the azobenzene-functionalized silane monolayer fiber film comprising an azobenzenesulfonyl chloride compound and a substrate;

[0006] Wherein, the azobenzenesulfonyl chloride compound comprises a connected azobenzene group and a sulfonyl chloride group.

[0007] Azobenzene (Azo-Benzene) is a class of aromatic compounds containing -N=N-. Its molecular structure is composed of two benzene rings connected by an azo group (-N=N-). Therefore, azobenzene compounds contain a conjugated π system and have a strong absorption peak between ultraviolet light and visible red light, which enables azobenzene to transform between cis-isomers and trans-isomers. Azobenzenesulfonyl chloride compounds containing azobenzene therefore also have the characteristics of photoisomerization. The principle of the conformational change of azobenzene molecules is as follows:

[0008]

[0009] The spinning technology can be used to spin a solution containing azobenzenesulfonyl chloride compounds into nano-scale fibers, forming a nanofiber membrane with a high specific surface area and a porous structure. The high specific surface area of ​​the nanofiber is conducive to the uniform distribution of the photoresponsive molecules and improves the photoresponsive efficiency of the membrane; the porous structure can increase the flexibility and mechanical properties of the membrane, making it less susceptible to damage during the light-driven friction transformation process.

[0010] Preferably, the substrate is a silicon substrate. The functionalized silicon (Si) substrate has high mechanical strength and stability, providing a solid support platform for the azobenzenesulfonyl chloride compound membrane, ensuring the structural integrity of the membrane during preparation and use. The silicon substrate usually has a very flat surface, which helps to form a uniform nanofiber membrane and improve the surface quality of the membrane.

[0011] Preferably, the substrate is a functionalized silicon substrate; the functionalized silicon substrate is a silicon substrate treated with a silane coupling agent, and the silane coupling agent is 3-aminopropyltriethoxysilane. 3-Aminopropyltrieth oxysilane (APTES) introduces amino (-NH2) groups on the surface of the silicon substrate through a chemical reaction. These amino groups provide chemically active sites for the subsequent grafting of azobenzenesulfonyl chloride compounds. Azobenzenesulfonyl chloride compounds form covalent bonds with the APTES functionalized Si substrate layer through amino groups, thereby firmly adhering to the surface of the Si substrate to prevent the film from falling off or being damaged during the light-driven friction transformation process.

[0012] Preferably, the 4th position of the azobenzene group further includes an R group; the R group is any one of -N(CH3)2, -COOH, -OH, -CH3, -CH2CH3. Among the R groups, -N(CH3)2 (dimethylamino), -COOH (carboxyl), -OH (hydroxyl) are hydrophilic groups; -CH3 (methyl) and -CH2CH3 (ethyl) are hydrophobic groups.

[0013] Preferably, the sulfonyl chloride group is located at the meta or para position of the azobenzene group. If the sulfonyl chloride group is located at the para position of the azobenzene group, the azobenzenesulfonyl chloride compound in the prepared azobenzene functionalized silane monolayer fiber membrane is vertically distributed on the APTES functionalized silicon Si substrate; if the sulfonyl chloride group is located at the meta position of the azobenzene group, there is a certain tilt angle between the azobenzenesulfonyl chloride compound and the APTES functionalized silicon Si substrate.

[0014] The azobenzenesulfonyl chloride compound of the present invention is selected from 4-dimethylaminophenylazobenzenesulfonyl chloride (DABS-Cl), and its molecular structure is 4-Carboxyazobenzenesulfonyl chloride, its molecular structure is 4-Hydroxyazobenzenesulfonyl chloride, its molecular structure is 4-Methylazobenzenesulfonyl chloride, its molecular structure is

[0015] for 4-Ethylazobenzenesulfonyl chloride, its molecular structure is 4-Azobenzene-4'sulfonyl chloride, its molecular structure is 4-Dimethylaminophenylazobenzene-5'-sulfonyl chloride, its molecular structure is 4-Carboxyazobenzene 5'-sulfonyl chloride, its molecular structure is 4-Hydroxyazobenzene 5'-sulfonyl chloride, its molecular structure is 4-Methylazobenzene 5'-sulfonyl chloride, its molecular structure is 4-Ethylazobenzene 5'-sulfonyl chloride, its molecular structure is Or 4-azobenzene 5'-sulfonyl chloride, its molecular structure is

[0016] As a general technical concept, the present invention also provides a method for using a light-driven friction reversible conversion film, wherein when the film is in a first state, ultraviolet light is irradiated on the film to obtain a film in a second state;

[0017] When the film is in the second state, the film is irradiated with visible light or mechanical force is applied to obtain a film in the first state; wherein the azobenzene groups in the film in the first state are in a trans conformation, and the azobenzene groups in the film in the second state are in a cis conformation.

[0018] Preferably, the mechanical force is applied by an atomic force microscope, and the visible light is blue light. In the present invention, the mechanical force of an atomic force microscope (AFM) is used to induce the direct cis-trans isomerization of azobenzene functionalized silane monolayer. AFM is a high-resolution surface analysis tool that can be used to observe and measure the morphology, mechanical properties, electrical properties, etc. of the sample surface. The working principle of AFM is based on the interaction force between the probe and the sample surface, and a three-dimensional image of the sample surface is constructed by detecting the changes in these forces. Different from the method of stretching azo bonds in the traditional way, the atomic force microscope introduces mechanical force with a vector, which actually compresses the molecule instead of stretching it. This force provides the energy required for the release of the metastable cis conformation and triggers the conversion process into the lower energy trans conformation.

[0019] As a general technical concept, the present invention also provides a method for preparing a light-driven friction reversible conversion film, comprising the following steps:

[0020] (1) ultrasonically cleaning the silicon substrate and then performing a hydroxylation treatment, drying it with a protective gas, immersing it in a freshly prepared 0.04M 3-aminopropyltriethoxysilane organic solution for mixing and reaction, and drying it with a protective gas after cleaning to obtain a 3-aminopropyltriethoxysilane functionalized silicon substrate;

[0021] (2) dissolving an azobenzenesulfonyl chloride compound in an organic solvent, stirring the mixture until the compound is completely dissolved, and preparing a spinning solution;

[0022] (3) injecting the spinning solution prepared in step (2) into the injection pump of the electrospinning machine, starting electrospinning, ejecting filaments, and depositing them on the 3-aminopropyltriethoxysilane functionalized silicon substrate prepared in step (1), thereby forming an azobenzene functionalized silane nanofiber membrane;

[0023] (4) Drying the azobenzene-functionalized silane nanofiber membrane obtained in step (3) to remove the residual solvent, and then curing the membrane to obtain a light-driven friction reversible conversion membrane.

[0024] Preferably, in the step (1), the silicon substrate is ultrasonically cleaned using acetone, ethanol and deionized water, respectively, 3 times for each, each time for 5 minutes; the hydroxylation treatment is performed by immersing the Si substrate in a solution of concentrated sulfuric acid and hydrogen peroxide in a volume ratio of 7:3 for 15 minutes; and the protective gas is argon.

[0025] Preferably, the organic solvent in step (1) is methanol; the methanol solution of 3-aminopropyltriethoxysilane is prepared by mixing methanol with deionized water, adjusting the pH to 4.5-5.5 with 1 mM acetic acid, then adding 3-aminopropyltriethoxysilane, and stirring at room temperature for 5 minutes, wherein the volume proportion of methanol is 94%, the volume proportion of deionized water is 5%, and the volume proportion of 3-aminopropyltriethoxysilane is 1%; then, the mixture is rinsed with a mixed solution of water: ethanol (V:V=1:1) and ethanol, and blown dry with argon.

[0026] Preferably, in step (2), the organic solvent is acetone, and the mass ratio of the azobenzenesulfonyl chloride compound to acetone is 1:10-30.

[0027] Preferably, the electrospinning parameters in the step (3) are: voltage 10-30 kV, spinning solution supply rate 0.1-1.0 mL / h, receiving distance 10-20 cm; in the step (3), the drying temperature is 60-80 ° C, and the drying time is 2-4 h; the curing method is heat treatment, the temperature is 100-150 ° C, and the treatment time is 1-3 h.

[0028] Compared with the prior art, the present invention has the following beneficial effects:

[0029] (1) The nanofiber membrane prepared from azobenzenesulfonyl chloride compounds and APTES functionalized silicon substrate, under UV irradiation, realizes the transformation from trans conformation to cis conformation, and the membrane enters the second state, the azobenzene molecules in the membrane fold, the surface height decreases, the area occupied by a single molecule increases, the contact area increases, and the friction increases; under blue light irradiation or AFM mechanical force, the cis conformation is transformed into trans conformation, and the azobenzene membrane is converted back to the first state, the extended state, the surface height increases, the area occupied by a single molecule decreases, the contact area decreases, and the friction decreases. Therefore, the conformation of azobenzene molecules in the membrane can be changed by irradiating different light and applying AFM mechanical force, and isomerization also changes its friction, thereby realizing light-driven reversible friction transformation.

[0030] (2) Atomic force microscopy introduces a mechanical force as a vector by compressing the molecule, providing the energy required to release the metastable cis conformation and triggering the conversion process into the lower energy trans conformation. Moreover, the application of local mechanical force can induce cis-trans isomerization of the monolayer throughout the entire area, achieving a large range of photoresponsive changes and promoting monolayer cis-trans nanolithography (CTNL).

[0031] (3) The prepared azobenzene-functionalized nanofiber membrane has good mechanical strength and flexibility, and can maintain structural integrity and stability during light-driven friction transformation. This allows the membrane to maintain good performance during multiple light-driven friction transformations. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] The present invention will be further described below in conjunction with the accompanying drawings.

[0033] Figure 1 Schematic diagram of the photoisomerization change of the light-driven friction reversible conversion film prepared in Example 1 under different light and mechanical forces.

[0034] Figure 2 This is a surface scanning electron microscope (SEM) image of the light-driven friction reversible switching film prepared in Example 1.

[0035] Figure 3 This is a graph showing the height and friction changes of the light-driven friction reversible conversion film prepared in Example 1 before and after UV light irradiation.

[0036] Figure 4 This is a graph showing the changes in height and friction of the light-driven friction reversible conversion film prepared in Example 1 after exposure to blue light or using AFM mechanical force.

[0037] Figure 5 This is a curve diagram of the height and friction force changes of the light-driven friction reversible conversion film prepared in Example 1 after being exposed to blue light or using AFM mechanical force. DETAILED DESCRIPTION

[0038] The technical solutions in the embodiments of the present invention are described in detail below, and the described embodiments are only some embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field belong to the protection scope of the present invention.

[0039] The present invention provides a light-driven reversible electrospinning membrane, comprising azobenzene groups and sulfonyl chloride groups connected together and a substrate. The azobenzene group is the core component of the electrospinning membrane, which is a type of molecular switch that can undergo photoisomerization. The substrate is selected from 1.5 cm 2 Si <100> Substrate (p-Si, highly doped), Si <100> The silicon material of the crystal surface has good mechanical strength and stability, which is conducive to maintaining the integrity of the substrate and the mechanical properties of the final product in the subsequent preparation of the reversible transformation membrane; the p-type Si substrate is suitable for preparing materials with specific optical absorption characteristics. The Si substrate is surface modified using APTES. The amino group at the end of the APTES molecule can serve as the active site for connecting the molecule, thereby promoting the subsequent chemical reaction with azobenzenesulfonyl chloride compounds, so that the azobenzene molecules are smoothly grafted onto the silicon substrate; the silane group in the APTES molecule can form a covalent bond on the surface of the silicon substrate, thereby enhancing the adhesion of the azobenzenesulfonyl chloride compounds to the silicon substrate.

[0040] In the embodiment of the present invention, the 4-position of the azobenzene group may also include an R group, and the R group may be -N(CH3)2, -COOH, -OH, -CH3, -CH2CH 3, Among them, -N(CH3)2, -COOH, and -OH are hydrophilic groups, while -CH3 and -CH2CH3 are hydrophobic groups. The hydrophilicity and hydrophobicity of the R group will affect the adhesion of the final film. In this way, when the atomic force microscope is used for subsequent detection, the presence of the hydrophilic group will increase the roughness and polarity of the surface, causing the probe to apply greater force when scanning the membrane surface, thereby detecting greater friction; while the hydrophobic group will reduce the polarity and roughness of the surface, and the adhesion will be reduced during the probe detection, and the friction will also be reduced accordingly.

[0041] In the embodiment of the present invention, the sulfonyl chloride group can be located at the para position or the meta position of the azobenzene group. When the sulfonyl chloride group is located at the para position of the azobenzene group, in the finally prepared reversible transformation membrane, the azobenzenesulfonyl chloride compounds are vertically distributed on the APTES-functionalized silicon Si substrate, and the reversible transformation membrane prepared in this way has a flat surface, so when the AFM mechanical force is used to change its conformation, it is easier to change the reversible transformation membrane from the cis conformation to the trans conformation; if the sulfonyl chloride group is located at the meta position of the azobenzene group, in the finally formed membrane, the azobenzenesulfonyl chloride compounds are distributed on the APTES-functionalized silicon Si substrate at a certain tilt angle, and when the AFM mechanical force is used to change its conformation, the tilted azobenzenesulfonyl chloride compounds are arranged on the silicon substrate in a tilted manner, so the prepared reversible transformation membrane also presents a tilted state. Therefore, when the same mechanical force is applied, the conversion rate of the reversible transformation membrane from the cis conformation to the trans conformation is reduced, which increases the difficulty of AFM detection, and the conformational conversion effect of the prepared reversible transformation membrane is poor.

[0042] The present invention will be further described below in conjunction with the accompanying drawings and specific embodiments.

[0043] Example 1

[0044] A light-driven friction reversible conversion film, the film includes an azobenzene-functionalized silane monolayer fiber film, the azobenzene-functionalized silane monolayer film includes 4-dimethylaminophenylazobenzenesulfonyl chloride (DABS-Cl, ) and 3-aminopropyltriethoxysilane (APTES) functionalized silicon (Si) substrates.

[0045] The specific preparation method comprises the following steps:

[0046] (1) 1.5cm 2 Si <100> The substrate (p-Si, highly doped) was ultrasonically cleaned in acetone, ethanol and deionized water in turn, 3 times each, 5 minutes each time; then it was placed in a solution of concentrated sulfuric acid and hydrogen peroxide mixed in a volume ratio of 70%:30%, soaked for 15 minutes, cleaned with deionized water and then dried with argon gas;

[0047] (2) Methanol and deionized water were mixed in a volume ratio of 94%:5%, the pH was adjusted to 5.5 with 1 mM acetic acid, and then 1% by volume of APTES was added, and stirred at room temperature for 5 min to prepare a 0.04 M APTES methanol solution; the cleaned Si substrate was placed in the 0.04 M APTES methanol solution for 20 min, and then rinsed with a water:ethanol (V:V=1:1) mixed solution and ethanol, and dried with argon gas to obtain an APTES-functionalized Si substrate;

[0048] (3) dissolving DABS-Cl in acetone, with the mass ratio of DABS-Cl to acetone being 1:20, and stirring thoroughly until completely dissolved to prepare a spinning solution;

[0049] (4) injecting the spinning solution into the injection pump of the electrospinning machine at a supply rate of 1.0 mL / h, the electrospinning machine uses a voltage of 10 kV, and the receiving distance is 12 cm, and deposits it on the APTES-functionalized Si substrate to obtain an azobenzene-functionalized silane nanofiber membrane;

[0050] (5) The azobenzene functionalized silane nanofiber membrane was placed in an oven at 65°C and dried for 4 hours to remove the residual solvent. The membrane was then heat treated at 150°C for 2 hours to obtain a light-driven friction reversible conversion membrane.

[0051] Example 2

[0052] A light-driven friction reversible conversion film, the film includes an azobenzene-functionalized silane monolayer fiber film. The azobenzene-functionalized silane monolayer fiber film includes 4-dimethylaminophenylazobenzene-5'-sulfonyl chloride (molecular formula: ) and 3-aminopropyltriethoxysilane (APTES) functionalized silicon (Si) substrates.

[0053] The specific preparation method comprises the following steps:

[0054] (1) 1.5cm 2 Si <100> The substrate (p-Si, highly doped) was ultrasonically cleaned in acetone, ethanol and deionized water, three times each, 5 minutes each time; then it was placed in a piranha solution made of a mixture of concentrated sulfuric acid and hydrogen peroxide in a volume ratio of 70%:30%, soaked for 15 minutes, cleaned with deionized water and then dried with argon gas;

[0055] (2) Methanol and deionized water were mixed in a volume ratio of 94%:5%, the pH was adjusted to 4.5 with 1 mM acetic acid, and then 1% by volume of APTES was added, and stirred at room temperature for 5 minutes to prepare a 0.04 M APTES methanol solution; the cleaned Si substrate was placed in the 0.04 M APTES methanol solution for 20 minutes, and then rinsed with a water:ethanol (V:V=1:1) mixed solution and ethanol, and dried with argon gas to obtain an APTES-functionalized Si substrate;

[0056] (3) dissolving 4-dimethylaminophenylazobenzene-5'-sulfonyl chloride in acetone, wherein the mass ratio of 4-dimethylaminophenylazobenzene-5'-sulfonyl chloride to acetone is 1:15, and stirring the mixture until the mixture is completely dissolved to prepare a spinning solution;

[0057] (4) injecting the spinning solution into the injection pump of the electrospinning machine at a supply rate of 0.1 mL / h, the electrospinning machine uses a voltage of 15 kV, and the receiving distance is 10 cm, and deposits it on the APTES-functionalized Si substrate to obtain an azobenzene-functionalized silane nanofiber membrane;

[0058] (5) The azobenzene functionalized silane nanofiber membrane was placed in an oven at 60°C and dried for 3 hours to remove the residual solvent. The membrane was then heat treated at 100°C for 3 hours to obtain a light-driven friction reversible conversion membrane.

[0059] Comparative Example 1

[0060] A light-driven friction reversible switching film composed of azobenzene monomers.

[0061] The specific preparation method comprises the following steps:

[0062] (1) dissolving azobenzene in acetone with a mass ratio of azobenzene to acetone being 1:10, stirring thoroughly until completely dissolved, and preparing a spinning solution;

[0063] (2) injecting the spinning solution into the injection pump of the electrospinning machine at a supply rate of 0.5 mL / h, the electrospinning machine uses a voltage of 20 kV and a receiving distance of 20 cm to obtain an azobenzene functionalized nanofiber membrane;

[0064] (3) The azobenzene functionalized nanofiber membrane was placed in an oven at 80°C and dried for 2 hours to remove the residual solvent. The nanofiber membrane was then heat treated at 130°C for 1 hour to obtain a light-driven friction reversible conversion membrane.

[0065] Comparative Example 2

[0066] A film made from polylactide.

[0067] The specific preparation method comprises the following steps:

[0068] (1) dissolving 10 g of polylactide in 100 g of hexafluoroisopropanol to prepare a polylactide solution, and stirring thoroughly to obtain an electrospinning membrane solution;

[0069] (2) The electrospinning membrane solution was injected into the injection pump of the electrospinning machine at a flow rate of 1 mL / h. The electrospinning machine used a voltage of 12 kV and a receiving distance of 14 cm to obtain a polylactide membrane.

[0070] The products prepared in Example 1-2 and the products prepared in Comparative Example 1-2 were selected for testing:

[0071] The surface adhesion, friction, and surface height of the prepared reversible transformation film were tested by applying ultraviolet light and AFM mechanical force.

[0072] Ultraviolet (UV) irradiation parameters: UV light wavelength: 365nm; UV irradiation time: 208s, irradiating the sample surface to cause the trans conformation to change to the cis conformation.

[0073] AFM mechanical force parameters: LFM mode, 30nN load applied by AFM, scanning area 5×5μm 2 , controlling the change from cis conformation to trans conformation.

[0074] Combination Figure 1 and Figure 3 After the film prepared in Example 1 was irradiated with ultraviolet light of wavelength 365nm for 208s, the trans conformation was converted to the cis conformation, the azobenzene group in DABS was folded, the surface height was reduced, but the contact area was increased, and the friction force was also increased; combined with Figure 4 and Figure 5 It is known that when irradiated with blue light or AFM mechanical force is applied, the film returns from the cis conformation to the trans conformation, the azobenzene group in DABS expands, the surface height increases, but the contact area decreases accordingly, so that the friction force is reduced. And due to the presence of the dimethylamino hydrophilic group in DABS, when the AFM mechanical force is applied, the adhesion between the probe tip of AFM and the film surface increases, so that the friction force is also increased. And in Example 2, 4-dimethylaminophenylazobenzene-5'-sulfonyl chloride is used to prepare a reversible conversion film, and its sulfonyl chloride group is located in the meta position of the azobenzene group, and the prepared film is in a tilted state. When a mechanical force of 30nN load is also applied to it, the conversion rate of its cis conformation back to the trans conformation decreases, thereby causing the effect of friction change to deteriorate.

[0075] Comparative Example 1 is a reversible transformation film prepared using azobenzene monomer. Although the azobenzene monomer can still undergo photoisomerization, the absence of R groups and the presence of a substrate makes it have no adhesion and the friction force does not change much. The film prepared without azobenzene molecules in Comparative Example 2 is even more unable to change the friction force under the action of light or mechanical force.

[0076] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the technical principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A light-driven friction reversible conversion film, characterized in that: The light-driven friction reversible conversion film comprises an azobenzene-functionalized silane monolayer fiber film, and the azobenzene-functionalized silane monolayer fiber film comprises an azobenzenesulfonyl chloride compound and a substrate; Wherein, the azobenzenesulfonyl chloride compound comprises a connected azobenzene group and a sulfonyl chloride group.

2. The light-driven friction reversible switching film according to claim 1, characterized in that: The substrate is a silicon substrate.

3. The light-driven friction reversible switching film according to claim 1, characterized in that: The substrate is a functionalized silicon substrate; the functionalized silicon substrate is a silicon substrate treated with a silane coupling agent, and the silane coupling agent is 3-aminopropyltriethoxysilane.

4. The light-driven friction reversible switching film according to claim 1, characterized in that: The 4th position of the azobenzene group also includes an R group; the R group is any one of -N(CH3)2, -COOH, -OH, -CH3, and -CH2CH3.

5. The light-driven friction reversible switching film according to claim 1, characterized in that: The sulfonyl chloride group is located at the meta-position or para-position of the azobenzene group.

6. A method for using a light-driven friction reversible conversion film according to any one of claims 1 to 5, characterized in that: include: When the film is in a first state, irradiating the film with ultraviolet light to obtain a film in a second state; When the film is in the second state, the film is irradiated with visible light or mechanical force is applied to obtain a film in the first state; wherein the azobenzene groups in the film in the first state are in a trans conformation, and the azobenzene groups in the film in the second state are in a cis conformation.

7. The method for using a light-driven friction reversible conversion film according to claim 6, characterized in that: The mechanical force is applied by an atomic force microscope, and the visible light is blue light.

8. A method for preparing a light-driven friction reversible switching film according to any one of claims 1 to 5, characterized in that: The following steps are involved: (1) ultrasonically cleaning the silicon substrate and then performing a hydroxylation treatment, drying it with a protective gas, immersing it in a freshly prepared 0.04M 3-aminopropyltriethoxysilane organic solution for mixing and reaction, and drying it with a protective gas after cleaning to obtain a 3-aminopropyltriethoxysilane functionalized silicon substrate; (2) dissolving an azobenzenesulfonyl chloride compound in an organic solvent, stirring the mixture until the compound is completely dissolved, and preparing a spinning solution; (3) injecting the spinning solution prepared in step (2) into the injection pump of the electrospinning machine, starting electrospinning, ejecting filaments, and depositing them on the 3-aminopropyltriethoxysilane functionalized silicon substrate prepared in step (1), thereby forming an azobenzene functionalized silane nanofiber membrane; (4) Drying the azobenzene-functionalized silane nanofiber membrane obtained in step (3) to remove the residual solvent, and then curing the membrane to obtain a light-driven friction reversible conversion membrane.

9. The method for preparing a light-driven friction reversible switching film according to claim 8, characterized in that: In the step (1), the silicon substrate is selected from 1.5 cm 2 Si <100> The substrate is p-type; the silicon substrate is placed in a mixed solution prepared by concentrated sulfuric acid and hydrogen peroxide in a volume ratio of 7:3 for hydroxylation treatment; the protective gas is argon; the organic solvent in the step (2) is acetone, and the mass ratio of azobenzenesulfonyl chloride compound to acetone is 1:10-30.

10. The method for preparing a light-driven friction reversible switching film according to claim 8, characterized in that: The electrospinning parameters in the step (3) are: voltage 10-30 kV, spinning solution supply speed 0.1-1.0 mL / h, receiving distance 10-20 cm; in the step (4), the drying temperature is 60-80° C., and the drying time is 2-4 h; the curing treatment method is heat treatment, the temperature is 100-150° C., and the treatment time is 1-3 h.

Citation Information

Patent Citations

  • Method for carrying out surface wettability regulation and control by photostimulation response substance modification shape memory polymer

    CN107501589A

  • Photosensitive chromatographic stationary phase based on silicon substrate modified by azobenzene photosensitive compound

    CN110339827A

  • Light sensation driving fiber and preparation method thereof, light driving motor and light driving nano mechanical arm

    CN112144137A

  • Preparation and application research of light / acid-base dual stimuli responsive rigid polymer

    CN116376085A

  • Optically responsive material and its manufacturing method

    JP2004093996A